Comparison of the intestinal flora of wild and artificial breeding green turtles (Chelonia mydas) - Niu, Xin; Lin, Liu; Zhang, Ting; An, Xiaoyu; Li, Yupei; Yu, Yangfei; Hong, Meiling; Shi, Haitao; Ding, Li (Frontiers in Microbiology, 2024)
Gut microbes are pivotal reference indicators for assessing the health status of animals. Before introducing artificially bred species into the wild, examining their gut microbe composition is crucial to help mitigate potential threats posed to wild populations. However, gut microbiological trait similarities between wild and artificially bred green turtles remain unexplored. Therefore, this study compared the gut microbiological characteristics of wild and artificially bred green turtles (Chelonia mydas) through high-throughput Illumina sequencing technology. The α-diversity of intestinal bacteria in wild green turtles, as determined via Shannon and Chao indices, significantly surpasses that of artificial breeding green turtles (P < 0.01). However, no significant differences were detected in the fungal α-diversity between wild and artificially bred green turtles. Meanwhile, the β-diversity analysis revealed significant differences between wild and artificially bred green turtles in bacterial and fungal compositions. The community of gut bacteria in artificially bred green turtles had a significantly higher abundance of Fusobacteriota including those belonging to the Paracoccus, Cetobacterium, and Fusobacterium genera than that of the wild green turtle. In contrast, the abundance of bacteria belonging to the phylum Actinobacteriota and genus Nautella significantly decreased. Regarding the fungal community, artificially bred green turtles had a significantly higher abundance of Fusarium, Sterigmatomyces, and Acremonium and a lower abundance of Candida and Rhodotorula than the wild green turtle. The PICRUSt2 analyses demonstrated significant differences in the functions of the gut bacterial flora between groups, particularly in carbohydrate and energy metabolism. Fungal functional guild analysis further revealed that the functions of the intestinal fungal flora of wild and artificially bred green turtles differed significantly in terms of animal pathogens–endophytes–lichen parasites–plant pathogens–soil saprotrophs–wood saprotrophs. BugBase analysis revealed significant potential pathogenicity and stress tolerance variations between wild and artificially bred green turtles. Collectively, this study elucidates the distinctive characteristics of gut microbiota in wild and artificially bred green turtles while evaluating their health status. These findings offer valuable scientific insights for releasing artificially bred green turtles and other artificially bred wildlife into natural habitats.